The Influence of Promotion, Service Quality, and Customer Experience on Repurchase Intention in The Culinary Industry in Surabaya, Indonesia - Apreliana, Selvi; Hartini, Sri (Manunggal Halim Jaya, 2026)
This study examines the impact of promotion, service quality, and customer experience on repurchase intention in the culinary industry of Surabaya. Using a quantitative survey design, data were collected from 100 respondents who had visited Restaurant X at least twice in the past month. Validity and reliability tests confirmed the robustness of the measurement instrument (Cronbach's Alpha > 0.70). The findings indicate that service quality (β = 0.371, p = 0.002) and customer experience (β = 0.396, p = 0.000) significantly affect repurchase intention, while promotion (β = 0.123, p = 0.371) shows a positive but insignificant effect. The model explains 38% of the variance (R² = 0.380) in repurchase intention. These results highlight that restaurants should prioritize enhancing service quality and customer experience to foster loyalty rather than relying solely on promotions.